Gestão de bibliotecas universitárias híbridas e o uso de tecnologias em rede: um estudo de caso comparativo entre FURG e Unipampa - Fortes, Maria Fermina Santana (2017)
The present case study is a dissertation that has as a concentration area, Networked Educational Technologies for Innovation and Democratization of Education, and is part of the research line Management of Educational Technologies in Network within the scope of the Master in Educational Technologies in Network of the Federal University of Santa Maria (UFSM). The study aims to analyze the management of hybrid libraries and the use of networked technologies in the Federal University Rio Grande Central Library (FURG) and the Campus Bagé Library of the Federal University of Pampa (UNIPAMPA). The basic theory brings authors in the area of Library Science, Information Science and Administration to address: the issue of the librarian as manager of information and the influence of network technologies in hybrid university libraries, aiming to facilitate the access to information. The guiding problem of the present research seeks to identify: what are the limits and potentialities of library management in the use of networked technologies as a facilitating element of access to information for users of university libraries? It intends to contribute to critical reflections on the subject, and corroborates the need for a new information management proposal in the hybrid libraries researched, aiming at satisfactory user service. The approach adopted was hypothetical-deductive, and the procedures adopted were: bibliographic research, field research and documentary analysis. The technique adopted in the bibliographic research was: registration and abstracts. Field research was conducted through observation, interview and application of questionnaires to librarians, support staff and users of the FURG Central Library and the UNIPAMPA - Campus Bagé Library. In the documentary analysis, tables and graphics were used. The results obtained showed the need for the librarian to acquire new skills and to focus their activities on the user, aiming at access to information.